y^2+x^2-6y+5=0
If this is your starting equation
then:
x^2 + y^2 - 6y = -5
x^2 + y^2 - 6y + 9 = -5 + 9
x^2 + (y-3)^2 = 4
so centre of this circle is (0,3) and the radius is √4 or 2
the next two have "bouncing equal signs" , thus make no sense
the third one:
(y+3)^2-9-(x-2)^2=4
(y+3)^2 - (x-2)^2= 4 + 9
(x-2)^2 - (y+3)^2 = -13
this is a hyperbola with the foci on the y-axis
we don't use the term radius with hyperbolas.
I have no clue what the last one is, it sure looks like some typo variation
of the previous one.
Please help me if my answer is correct.
transform each equation into center radius form.
1. y2+x2-6y+5=0
y2+6y=(y+3)2=9
x2-5=(x-2)2=4
(y+3)2-9-(x-2)2=4
(y+3)2-9(x-2)2-4=+4
1 answer